The marketization of data elements, facilitation of cross-border capital flows, and regional green total factor productivity - Wang, Hao Liang; Wang, Zhong; Li, Jing Wen; Shan, Zheng (Elsevier Inc., 2026)
This paper empirically examines the mechanisms among the marketization of data elements (DataMarket), facilitation of cross-border capital flows, and regional green total factor productivity (RGTFP) based on panel data from Chinese cities from 2010 to 2023. The study finds that: first, DataMarket has a significant positive effect on RGTFP, and this effect exhibits notable heterogeneity across regions with varying intensities of environmental regulation. Second, the facilitation of cross-border capital flows serves as a significant mediating mechanism in the link between DataMarket and RGTFP. Third, as regional R&D investment rises, the positive impact of DataMarket on RGTFP exhibits pronounced threshold effects. This study offers empirical evidence for understanding how data elements contribute to green development and provides policy insights aimed at advancing the establishment of data factor markets, liberalizing capital accounts, and promoting green, low-carbon transitions.